2002
DOI: 10.1080/030097402317255372
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary miliary tuberculosis in a patient with anti-TNF-alpha treatment

Abstract: No difference in the number of serious adverse events was reported in previous clinical trials in rheumatoid arthritis (RA) and inflammatory bowel disease (IBD) patients treated with TNF-alpha blockade, but a patient died because of disseminated tuberculosis. A tuberculosis reactivation in a patient with IBD and anti-TNF-alpha treatment has been recently reported. Very recently 70 cases of tuberculosis were reported from the FDA Adverse Event Reporting System. We report a case of pulmonary miliary tuberculosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 0 publications
0
25
0
3
Order By: Relevance
“…These effects can vary from mild opportunistic diseases to tuberculosis or even multiple sclerosis. [32][33][34] Although the effective treatment of RA through anti-TNFa therapy, it appears from these studies that deprivation of this cytokine in some cases can result in severe impairment of the immune response. It is not unthinkable that systemic cytokine blocking therapies will eventually result in systemic impairment of innate and acquired immunity, while local therapies can be less interfering with systemic processes.…”
Section: Discussionmentioning
confidence: 99%
“…These effects can vary from mild opportunistic diseases to tuberculosis or even multiple sclerosis. [32][33][34] Although the effective treatment of RA through anti-TNFa therapy, it appears from these studies that deprivation of this cytokine in some cases can result in severe impairment of the immune response. It is not unthinkable that systemic cytokine blocking therapies will eventually result in systemic impairment of innate and acquired immunity, while local therapies can be less interfering with systemic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc deficiency was shown to decrease the production of tumour necrosis factor-a (TNFa) and gamma interferon (IFN-g) from peripheral mononuclear cells (Beck et al, 1997). It was also suggested that administration of anti-TNF-a to patients may lead to reactivation of TB (Mayordomo et al, 2002), and a mutation in the gene coding for the IFN-g receptor resulted in an increased susceptibility to mycobacterial infections (Newport et al, 1996). It therefore seems possible that zinc deficiency is implicated in the activation of TB.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-␣ regulates various lymphocyte functions, such as cell proliferation and IL-2R expression (19), and is critical for the progression of rheumatoid arthritis (20). The substantial role played by TNF-␣ during inflammation led to the development of different strategies to block its activity (21), although not all patients respond to these treatments, and they could be accompanied with severe side effects, such as the induction of tuberculosis (22). In this report, we examined the ability of LX and ATL to modulate extracellular signal-regulated kinase (ERK)-dependent TNF-␣ secretion from T cells.…”
mentioning
confidence: 99%